2023
DOI: 10.3390/pr11030957
|View full text |Cite
|
Sign up to set email alerts
|

Resonance-Enhanced Pulsing Water Injection for Improved Oil Recovery: Micromodel Experiments and Analysis

Abstract: Enhanced oil recovery (EOR) is a crucial technology in the petroleum industry, influenced by several factors, including flooding fluids and methods. The adjustment of injection strategies and the application of vibration stimulation can significantly impact oil recovery, especially residual oil. In this study, we conducted experiments using a glass micromodel to investigate the effect of pulsing water injection on oil recovery. Our results show that when the pulse frequency matches the natural frequency of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Surfactant flooding is one of the CEOR methods that has been successfully implemented for the past few decades; however, the environmental drawbacks of these chemical-based compounds have raised serious concerns about these materials. These chemical-based surfactants are toxic and nonenvironmentally friendly, restricting them from further development [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surfactant flooding is one of the CEOR methods that has been successfully implemented for the past few decades; however, the environmental drawbacks of these chemical-based compounds have raised serious concerns about these materials. These chemical-based surfactants are toxic and nonenvironmentally friendly, restricting them from further development [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Moradi et al extracted a new bio-based surfactant from the Tribulus Terrestris plant and used it for EOR in a carbonate oil reservoir. They also investigated the effects of different ions (Ca 2+ , Mg 2+ , SO 4 2− ) on the efficiency of the green surfactant during smart water flooding. Their findings revealed that SO 4 2− had the best impact on the green surfactant's performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation